Yoga, Sexual Violation and Discourse: Reconfigured Hegemonies and Feminist Voices. Issue 105 (2nd July 2020) - Black, Shameem
ABSTRACT: What can we learn from cultural practices that are simultaneously narrated as the cause and cure for sexual violation? In recent years, yoga has come to exemplify one such practice. The world of yoga has been roiled by accusations of violation, yet yoga has also gained prominence as a therapeutic tool and even as a policy recommendation to reduce assault. I analyse such competing rhetoric from India and the United States to shed light on how patriarchal and capitalist discourses can gain new vitality in the name of contesting violations they enable. Such cultural logics frame yoga-themed narratives solicited and archived under the sign of the #MeToo hashtag. Cultivating yoga as a feminist practice requires us to examine more radical visions found before and beyond #MeToo, exemplified within memoir and fiction.